2005
DOI: 10.1021/ie050842c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Sorption and Swelling Behavior of Semicrystalline Polymers in Supercritical CO2

Abstract: The effect of semicrystallinity on the sorption and swelling behavior of polymers in supercritical CO 2 is investigated. In particular, the experimental behavior measured for four different polymers in a previous work, i.e., poly(methyl methacrylate), poly(vinylidene fluoride), poly(tetrafluoroethylene), and the copolymer tetrafluoroethylene-perfluoromethylvinyl ether, is modeled using four different thermodynamic approaches: the Sanchez-Lacombe method in its nonequilibrium and equilibrium version, a modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 68 publications
3
53
1
Order By: Relevance
“…It can be observed that the average PMV of each gaseous component increases as its gas phase concentration decreases. However, the PMV dependence on gas phase concentration is higher for CH 4 than n-C4 which can be attributed to the higher interactions of CH 4 with the PDMS matrix (as indicated by the highly negative k 13 value in Figure 1-3 ) compared to n-C4. In addition, the temperature dependence of PMV is more pronounced for n-C4 than CH 4 probably due to higher thermal expansion of n-C4 than CH 4 (see the α values reported above).…”
Section: Methane(1)/n-butane(2)/pdms(3) Methane(1)/pdms(2) N-butane(1mentioning
confidence: 94%
See 3 more Smart Citations
“…It can be observed that the average PMV of each gaseous component increases as its gas phase concentration decreases. However, the PMV dependence on gas phase concentration is higher for CH 4 than n-C4 which can be attributed to the higher interactions of CH 4 with the PDMS matrix (as indicated by the highly negative k 13 value in Figure 1-3 ) compared to n-C4. In addition, the temperature dependence of PMV is more pronounced for n-C4 than CH 4 probably due to higher thermal expansion of n-C4 than CH 4 (see the α values reported above).…”
Section: Methane(1)/n-butane(2)/pdms(3) Methane(1)/pdms(2) N-butane(1mentioning
confidence: 94%
“…Once the mass fraction, m i , of each gas (or penetrant) in the polymer and the reduced mixture density, ρ , are calculated by solving the SL EoS, the mixture density, ρ , can be estimated by Equation ( 4) [ 3,4,31,33 ] …”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic studies have revealed the presence of a complex between poly(methyl methacrylate) and carbon dioxide. 4 The photoresist polymer, which has the same polymethacrylate backbone, could also form a complex with CO 2 that changes the interactions in the polymer-cosolvent systems. It is also possible that the presence of the cosolvents in the polymer enhanced the solubility of the CO 2 .…”
Section: Inverse Gas Chromatography Studiesmentioning
confidence: 99%